2020
DOI: 10.1016/j.pss.2020.105047
|View full text |Cite
|
Sign up to set email alerts
|

Obliquity dependence of the formation of the martian polar layered deposits

Abstract: Mars' polar layered deposits (PLD) are comprised of layers of varying dust-to-water ice volume mixing ratios (VMR) that are thought to record astronomically-forced climatic variation over Mars' recent orbital history. Retracing the formation history of these layers by quantifying the sensitivity of deposition rates of polar material to astronomical forcing is critical for the interpretation of this record. Using a Mars global climate model (GCM), we investigate the sensitivity of annual polar water ice and dus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…In addition to the atmospheric humidity described above, the evolution of surface ice was also tracked. Following past work (Emmett et al, 2020;Levrard et al, 2004Levrard et al, , 2007Madeleine et al, 2009), we track the evolution of surface ice at past orbital parameters. Here, we significantly extend the range of conditions studied, use more realistic ice distributions that are based on high obliquity GCM simulations and geologic evidence (Forget et al, 2006;Head et al, 2005), and provide interpretations based on the humidity patterns above, to derive a relation between polar cap growth rate and orbital elements.…”
Section: Thick Tropical Ice Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the atmospheric humidity described above, the evolution of surface ice was also tracked. Following past work (Emmett et al, 2020;Levrard et al, 2004Levrard et al, , 2007Madeleine et al, 2009), we track the evolution of surface ice at past orbital parameters. Here, we significantly extend the range of conditions studied, use more realistic ice distributions that are based on high obliquity GCM simulations and geologic evidence (Forget et al, 2006;Head et al, 2005), and provide interpretations based on the humidity patterns above, to derive a relation between polar cap growth rate and orbital elements.…”
Section: Thick Tropical Ice Reservoirmentioning
confidence: 99%
“…The length and intensity of the seasons are also governed by the eccentricity and perihelion precession, which have periods of 100 and 51 kyr, respectively. Previous modeling work using GCMs (Emmett et al, 2020;Levrard et al, 2004Levrard et al, , 2007) demonstrated that at low obliquity, when a tropical ice source is available, net transport of ice is from the equatorial region to the poles. Net polar ice gain occurs when obliquity is below a threshold of ∼35° for a circular orbit, but the precise value depends on other orbital elements, such as the perihelion position, and on assumed model parameters such as dust and ice properties (Madeleine et al, 2009).…”
mentioning
confidence: 99%
“…One caveat is that Emmett et al (2020) find that south polar dust deposition rate 𝑟 dust increases with increasing 𝜀. Specifically, they find, for 𝜀 = 15, 20, and 25 ∘ : 𝑟 dust = ~0.005 mm yr -1 ; for 𝜀 = 30 ∘ : 𝑟 dust = ~0.02 mm yr -1 , and for 𝜀 = 35 ∘ : 𝑟 dust = ~0.3 mm yr -1 .…”
Section: Previous Climate Model Predictions For 𝑟 𝐻 2 𝑂 − 𝑣𝑒𝑟𝑠𝑢𝑠 − 𝜀mentioning
confidence: 92%
“…In addition to the atmospheric humidity described above, the evolution of surface ice was also tracked. Following past work (Levrard et al, 2007;Emmett et al, 2020;Levrard et al, 2004;Madeleine et al, 2009), we track the evolution of surface ice at past orbital parameters. Here, we significantly extend the range of conditions studied, use more realistic ice distributions that are based on high obliquity GCM simulations and geologic evidence (Forget et al, 2006;Head et al, 2005), and provide interpretations based on the humidity patterns above, to derive a relation between polar cap growth rate and orbital elements.…”
Section: Thick Tropical Ice Reservoirmentioning
confidence: 99%
“…The length and intensity of the seasons are also governed by the eccentricity and perihelion precession, which have periods of 100 kyr and 51 kyr, respectively. Previous modeling work using GCMs (Levrard et al, 2004(Levrard et al, , 2007Emmett et al, 2020) demonstrated that at low obliquity, when a tropical ice source is available, net transport of ice is from the equatorial region to the poles. Net polar ice gain occurs when obliquity is below a threshold of ∼35 • for a circular orbit, but the precise value depends on other orbital elements, such as the perihelion position, and on assumed model parameters such as dust and ice properties (Madeleine et al, 2009).…”
Section: Introductionmentioning
confidence: 99%